State and Scholars: The Transformation of Islamic Astronomy in Late Ottoman Egypt - Alpaten, Ulil Albab Al aulia; Nugroho, Ayub; Rizqi, Deri (Institute of Research and Community Service UIN Prof. K.H. Saifuddin Zuhri, 2026)
This study explores the transformation of Islamic astronomy (‘ilm al-falak) in late Ottoman Egypt, emphasizing its role in religious authority, state formation, and scientific modernization. The research is urgent due to the epistemic shifts occurring during imperial transition, especially in Cairo’s religious and scientific institutions. Using historical-textual methods, the study analyzes archival records, mosque timekeeping documents, Arabic press debates, and translated astronomical tables. Postcolonial theory and science and technology studies serve as analytical tools to examine knowledge adaptation. The findings show that European astronomical models, such as French planetary tables, were localized within Islamic frameworks. Mechanical clocks were introduced into mosques, supervised by scholars, leading to standardized prayer times and the institutionalization of crescent moon observations. Religious scholars actively engaged with technological changes, integrating them within ethical and jurisprudential contexts. Public discourse in the Arab press reflected ongoing negotiations between modern science and religious tradition. Late Ottoman Egypt witnessed the hybridization of astronomical knowledge, shaped by political, religious, and technological forces. This process redefined the role of scholars in scientific discourse and laid the foundation for contemporary Islamic astronomy in the Middle East. This research contributes to the history of Islamic science by filling a critical gap in how scholars mediated the translation and institutionalization of European time technologies within Islamic religious frameworks, thereby reshaping the epistemic foundations of modern Islamic astronomy.